NMR characterization and membrane interactions of the loop region of kindlin-3 F1 subdomain - Chua, Geok-Lin (2018)
Kindlins-1,2 and 3 are FERM domain-containing cytosolic proteins involved in the activation and regulation of integrin-mediated cell adhesion. Apart from binding to integrin β cytosolic tails, kindlins and the well characterized integrin-activator talin bind membrane phospholipids. The ubiquitin-like F1 sub-domain of the FERM domain of talin contains a short loop that binds to the lipid membrane. By contrast, the F1 sub-domain of kindlins contains a long loop demonstrated binding to the membrane. Here, we report structural characterization and lipid interactions of the 83-residue F1 loop of kindlin-3 using NMR and optical spectroscopy methods. NMR studies demonstrated that the F1 loop of kindlin-3 is globally unfolded but stretches of residues assuming transient helical conformations could be detected in aqueous solution. We mapped membrane binding interactions of the F1 loop with small unilamellar vesicles (SUVs) containing either zwitterionic lipids or negatively charged lipids using 15N-1H HSQC titrations. These experiments revealed that the F1 loop of kindlin-3 preferentially interacted with the negatively charged SUVs employing almost all of the residues. By contrast, only fewer residues appeared to be interacted with SUVs containing neutral lipids. Further, CD and NMR data suggested stabilization of helical conformations and predominant resonance perturbations of the F1 loop in detergent containing solutions. Conformations of an isolated N-terminal peptide fragment, or EK21, of the F1 loop, containing a poly-Lys sequence motif, important for membrane interactions, were also investigated in detergent solutions. EK21 adopted a rather extended or β-type conformations in complex with negatively charged SDS micelles. To our knowledge, this is the first report describing the conformations and residue-specific interactions of kindlin F1 loop with lipids. These data therefore provide important insights into the interactions of kindlin FERM domain with membrane lipids that contribute toward the integrin activating property.